A survey for variable young stars with small telescopes – V. Analysis of TX Ori, V505 Ori, and V510 Ori, the HST ULLYSES targets in the σ Ori cluster. Issue 2 (27th November 2021) - Froebrich, Dirk; Eislöffel, Jochen; Stecklum, Bringfried; Herbert, Carys; Hambsch, Franz-Josef
ABSTRACT: Investigations of the formation of young stellar objects (YSOs) and planets require the detailed analysis of individual sources as well as statistical analysis of a larger number of objects. The Hubble UV Legacy Library of Young Stars as Essential Standards (ULLYSES) project provides such a unique opportunity by establishing a UV spectroscopic library of young high- and low-mass stars in the local universe. Here, we analyse optical photometry of the three ULLYSES targets (TX Ori, V505 Ori, V510 Ori) and other YSOs in the σ Ori cluster taken at the time of the HST observations to provide a reference for those spectra. We identify three populations of YSOs along the line of sight to σ Ori, separated in parallax and proper motion space. The ULLYSES targets show typical YSO behaviour with pronounced variability and mass accretion rates of the order of 10 −8 M⊙ yr −1 . Optical colours do not agree with standard interstellar reddening and suggest a significant contribution of scattered light. They are also amongst the most variable and strongest accretors in the cluster. V505 Ori shows variability with a 7 d period, indicating an inner disc warp at the co-rotation radius. Uncovering the exact nature of the ULLYSES targets will require improved detailed modelling of the HST spectra in the context of the available photometry, including scattered light contributions as well as non-standard reddening.